Fenomena Cyberbullying di Kalangan Remaja: Analisis Adaptasi Sosial dengan Pendekatan Teori Struktural Fungsional Talcott Parsons: Penelitian - Ida Fitriani; Sekarrini Solihan; Yohanes Bahari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The phenomenon of cyberbullying among adolescents represents a social consequence of rapid digital technological development that is not accompanied by sufficient preparedness in values and social control. Acts of online bullying have serious impacts on adolescents’ psychological and social conditions and demand adaptive responses from various elements of society. This study aims to analyze how individuals and social institutions respond to cyberbullying using Talcott Parsons’ Structural Functional theory through the AGIL scheme (Adaptation, Goal Attainment, Integration, and Latency). The method employed is a literature study, reviewing various recent scientific sources from the past five years relevant to the topic. The findings reveal that adolescents and institutions such as families, schools, and the state have engaged in social adaptation processes through the establishment of regulations, the reinforcement of moral values, and collective social integration. The AGIL theory proves effective in systematically explaining how social systems maintain balance when facing dysfunction caused by cyberbullying. This research contributes theoretically by strengthening the functionalist approach to contemporary social issues and practically by supporting efforts to protect and empower adolescents in the digital era.